Natural killer cell activity is a risk factor for the recurrence risk after curative treatment of hepatocellular carcinoma - Lee, Han Ah; Goh, Hyun Gil; Lee, Young-Sun; Jung, Young Kul; Kim, Ji Hoon; Yim, Hyung Joon; Lee, Min-Goo; An, Hyunggin; Jeen, Yoon Tae; Yeon, Jong Eun; Byun, Kwan Soo; Seo, Yeon Seok (BMC gastroenterology, 2021)
Background Natural killer (NK) cells have been known to contribute to surveillance and control of hepatocellular carcinoma (HCC). However, the association of NK cell activity with stage and recurrence risk of HCC have not been fully evaluated. Methods Untreated patients with newly diagnosed HCC were prospectively enrolled. Peripheral blood mononuclear cells were isolated at the time of diagnosis. Patients who had undergone surgery or radiofrequency ablation were classified as the curative treatment group, and their blood samples were collected again at 1 month after treatment. Results A total of 80 patients with HCC were enrolled. The mean age was 62.5 years. At baseline, interferon (IFN)-γ producing NK cell proportion was significantly lower in patients with Barcelona clinic liver cancer (BCLC) stage B, C, or D than in those with BCLC stage 0 (42.9% vs. 56.8%, P = 0.045). Among all patients, 56 patients had undergone curative treatment, and 42 patients re-visited at 1 month after curative treatment. There was no significant change in total NK cell and IFN-γ producing NK cell proportion from baseline to 1 month after treatment (all P > 0.05). During a median follow-up of 12.4 months, HCC recurred in 14 patients (33.3%). When patients were classified according to the IFN-γ producing NK cell proportion (group 1, ≥ 45%; and group 2, < 45%), HCC recurrence rate did not differ according to the IFN-γ producing NK cell proportion at baseline (log-rank test, P = 0.835). However, patients with < 45% IFN-γ producing NK cell proportion at 1 month after treatment had a significantly higher HCC recurrence rate than patients with that of ≥ 45% (log-rank test, P < 0.001). Multivariate analysis revealed that BCLC stage B (hazard ratio [HR] = 3.412, P = 0.045) and < 45% IFN-γ producing NK cell proportion at 1 month after treatment (HR = 6.934, P = 0.001) independently predicted an increased risk of HCC recurrence. Conclusions Decreased NK cell activity is significantly associated with the advanced stage of HCC, and the increased recurrence risk of HCC after curative treatment.